EMPIRICAL INVESTIGATION OF DETERMINANT FACTORS OF COMPANY DELISTING: EVIDENCE FROM INDONESIA - Leslie Benny; Yanthi Hutagaol (Journal of Applied Finance & Accounting, 2013)
The main purpose of the research is to evaluate determinant factors which contribute to companies being delisted from Stock Exchange Market in Indonesia. The samples are taken from the delisted companies list in IDX for a period year 2007-2011. The matching companies are then selected based on the company size to make an equivalent comparison for each delisted companies sample. The total final samples consist of 58 companies, 29 delisted companies and 29 matching companies. This research analyzes the company’s financial status by using descriptive statistics, independent sample t-test, and logistic regression model to find the effect of each determinant to the probability of delisting. The shares liquidity is a significant determinant to company’s delisting in Indonesia. Meanwhile, profitability and leverage seems to be determinant factors for delisted, but appear to be insignificant. Other examined factors, market capitalization and growth opportunity appear to insignificant determinants. This manager implication of this research is that the strong delisting factor is the external company factor, in this case, the market factor.